Resilient annular finite‐time synchronization for master‐slave systems under scaling attacks - Sathishkumar Murugesan; Takayuki Ishizaki; Yen‐Chen Liu (IET Control Theory & Applications, 2023)
Abstract This paper investigates the resilient annular finite‐time synchronization and boundedness problems for master‐slave systems under dynamic event‐triggered scheme (ETS), actuator faults, and scaling attacks. A comprehensive model for characterizing scaling attacks is presented. The switched dynamic ETS is developed to reduce the bandwidth pressure. Two different internal variables are designed, each of which changes based on the switching manifold. Simultaneously, the resilient problem of switched master‐slave systems with respect to stochastic scaling attacks is considered, where there are limited malicious signals introduced by the adversary. Based on the Lyapunov‐like function involving the different internal dynamic variables, a set of criteria is established in the form of linear matrix inequalities (LMIs), which guarantee the annular finite‐time boundedness. Finally, two examples are presented to verify the theoretical findings.